2016
DOI: 10.1021/acs.jpcb.5b12537
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Dance of the Two Conformers of Bis(trifluoromethanesulfonyl)imide as a Function of Pressure and Temperature

Abstract: Absorbance spectra of two ionic liquids, the short alkyl chain N-trimethyl-N-propylammonium bis(trifluoromethanesulfonyl)imide (TMPA-TFSI) and the longer chain N-trimethyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide (TMHA-TFSI) are reported as a function of pressure and temperature. The occurrence of various phase transitions is evidenced by the changes in the relative concentration of the cisoid and transoid conformers of their common TFSI anion. The infrared spectrum of TMPA-TFSI was measured at 300 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 37 publications
8
57
1
Order By: Relevance
“…After pressurization to 1 GPa, one can note the absence of the spectral line that, at room pressure, is centered around 327 cm −1 , due to cis ‐TFSI . This finding is consistent with infrared spectroscopy measurements performed on TMPA‐TFSI, which indicated that between 0.1 and 0.2 GPa, the system crystallizes into a structure containing trans ‐TFSI only …”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…After pressurization to 1 GPa, one can note the absence of the spectral line that, at room pressure, is centered around 327 cm −1 , due to cis ‐TFSI . This finding is consistent with infrared spectroscopy measurements performed on TMPA‐TFSI, which indicated that between 0.1 and 0.2 GPa, the system crystallizes into a structure containing trans ‐TFSI only …”
Section: Resultssupporting
confidence: 86%
“…We want to remark that the present Raman measurements are collected with the DAC gasket hole completely filled by the sample, whereas in the case of the infrared spectroscopy measurements reported in Capitani et al, part of the gasket hole was filled with KBr, in order to avoid the saturation of the bands recorded in transmission mode. In the present study, we wanted to study the pure ILs and mixtures, without the addition of other compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17] However, in the intermediate concentration range no crystalline state develops, but only a glass phase. [19,20] In fact, TMPA-TFSI crystallizes at room temperature as soon as a pressure of 0.2 GPa is applied, retaining the trans conformer of TFSI. [17,18] The behavior of the two ILs and of their mixtures is even more complex when a pressure is applied.…”
Section: Introductionmentioning
confidence: 99%